The bazaar effect, unbundling of comparative advantage, and migration - Wilhelm K. Kohler (Center for Economic Studies and ifo Institute (CESifo), 2007)
Germany exhibits a strong reduction in domestic manufacturing production depth (bazaar effect). I argue that this reflects an unbundling of comparative advantage. Using a model where Ricardian plus Heckscher-Ohlin-type comparative advantage relates to fragments of production, I compare a trading equilibrium where all fragments are located within a country with an equilibrium where input sub-bundles may be traded (offshoring). The model allows for several goods and two fragments, produced with high-skilled and low-skilled labor. I address wage and welfare effects under flexible wages, and under a minimum wage. I also explore trade policy implications and compare offshoring to migration.
Keywords: F11; F16; F22; 330; comparative advantage; offshoring; outsourcing; globalization; migration; Wertschöpfung; Industrielle Produktion; Lohnfertigung; Outsourcing; Außenwirtschaft; Auslandsproduktion; Globalisierung; Komparativer Kostenvorteil; Arbeitsteilung; Mindestlohn; Internationale Arbeitsmobilität; Theorie; Deutschland